2015
DOI: 10.1103/physrevd.91.124017
|View full text |Cite
|
Sign up to set email alerts
|

Entangled squeezed states in noncommutative spaces with minimal length uncertainty relations

Abstract: We provide an explicit construction of entangled states in a noncommutative space with nonclassical states, particularly with the squeezed states. Noncommutative systems are found to be more entangled than the usual quantum mechanical systems. The noncommutative parameter provides an additional degree of freedom in the construction by which one can raise the entanglement of the noncommutative systems to fairly higher values beyond the usual systems. Despite of having classical-like behaviour, coherent states i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 50 publications
1
67
0
Order By: Relevance
“…In this article, we propose yet another alternative way to obtain a squeezed atom laser by using a model, which not only has a strong mathematical ground originating from the quantum group, but also it demonstrates ample interesting results in generating squeezed states and in other aspects of quantum optics [21][22][23][24][25]. Previously, it was shown that the optical squeezing properties are inherited in these models by construction, here we show that it is true for the atom laser case also.…”
Section: Squeezed Atom Laser For Bec With Minimal Lengthmentioning
confidence: 58%
See 1 more Smart Citation
“…In this article, we propose yet another alternative way to obtain a squeezed atom laser by using a model, which not only has a strong mathematical ground originating from the quantum group, but also it demonstrates ample interesting results in generating squeezed states and in other aspects of quantum optics [21][22][23][24][25]. Previously, it was shown that the optical squeezing properties are inherited in these models by construction, here we show that it is true for the atom laser case also.…”
Section: Squeezed Atom Laser For Bec With Minimal Lengthmentioning
confidence: 58%
“…The corresponding observables X and P are represented in terms of the usual canonical variables x, p satisfying [x, p] = i . The model (2.1) has been explored extensively to construct coherent states, squeezed states, etc., as well as their physical implications have been discussed [22,23,25]. One interesting aspect of such model is that it can be associated with standard nonlinear generalized models by using some mathematical techniques.…”
Section: Minimal Length and Generalised Uncertainty Principlementioning
confidence: 99%
“…Enhancement of entanglement in non-commutative space has been explored in details [52]. This raises a question whether deformed space structure can give a boost to the quantum engines under study.…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting structures exist in the literature which leads to instances like minimal length and generalized version of Heisenberg's uncertainty relations. These are obtained when θ µν is considered to be a function of the coordinates and momenta [4,5].…”
Section: Introductionmentioning
confidence: 99%